2000
DOI: 10.1007/s00223001096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Estrogen and Progesterone on Tibia Histomorphometry in Growing Rats

Abstract: The present study was performed to evaluate possible interactions between estrogen and progesterone on peak cancellous bone mass. Ovariectomized (OVX) growing rats were treated with 17beta-estradiol (4.8 microg/day), progesterone (4.8 mg/day), a combination of the two sex steroids, or with vehicle for 14 days beginning 7 days after OVX. The tibiae were removed for histomorphometric analysis of the proximal metaphysis. OVX and growth each resulted in net resorption of cancellous bone at a sampling site adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 17 publications
0
26
0
2
Order By: Relevance
“…1D). In mammals, it was shown that progesterone has a stimulatory effect on bone formation in female rats and thus has the potential to influence skeletal growth in vertebrates (Schmidt et al, 2000). Direct testing of the effect of progesterone on female growth in squamates should therefore be pursued in the future.…”
Section: Discussionmentioning
confidence: 99%
“…1D). In mammals, it was shown that progesterone has a stimulatory effect on bone formation in female rats and thus has the potential to influence skeletal growth in vertebrates (Schmidt et al, 2000). Direct testing of the effect of progesterone on female growth in squamates should therefore be pursued in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[154] Peak tor β (TGFβ). [166] Some hormones, such as esadult level trabecular BMD measured by QCT is trogen, [167] inhibit proliferation of both osteoblasts achieved at the time of cessation of longitudinal and osteoclasts. Other, and sometimes the same, growth and closure of epiphyseal growth zones at hormones and growth factors can stimulate both about age 19 years.…”
Section: Messengers That Influence Bonementioning
confidence: 99%
“…In conjunction with by adipocytes in proportion to the size of body fat progesterone, estradiol reduces osteoclast activity, mass, [212] is another hormone that plays an important preserves trabecular bone and has overall anabolic role in both bone cell proliferation and differentia-action in bone. [167] Finally, cortisol inhibits osteotion. Leptin is hypothesised to promote longitudinal blast apoptosis.…”
Section: Messengers That Influence Bonementioning
confidence: 99%
See 1 more Smart Citation
“…Um dos fatores que podem ser apontados para justificar a diferença na intensidade da osteopenia da tíbia em comparação aos demais ossos longos foi o maior crescimento longitudinal desse osso na associação hipotireoidismo-castração, quando comparado ao grupo hipotireóideo não castrado (tabela 3). Essa observação é importante, pois a tíbia é um dos ossos mais utilizados como modelo para os estudos do metabolismo ósseo nas disfunções endócrinas (18,(47)(48)(49). Mas, no presente estudo, ficou claramente demonstrado que a resposta da tíbia às disfunções das gônadas e da tireóide é específica e não segue o mesmo padrão dos demais ossos.…”
Section: Grupo Hipotireóideo Castradounclassified